Choosing Xamarin Platform for App Development - Gokul Ramadoss (North American Journal of Engineering Research, 2023)
Selecting the appropriate platform for app development is crucial for ensuring efficiency, cost-effectiveness, and performance. This article delves into the Xamarin platform, a robust framework for cross-platform app development using C# and .NET. We compare Xamarin with other popular frameworks like React Native and Flutter, evaluating their strengths and weaknesses in terms of performance, scalability, cost, and developer experience. The findings are based on thorough research and real-world case studies, offering insights and recommendations for developers and businesses considering Xamarin for their next app development project.